Connect with us

How Do You Expand \( (x-3)^2 \)?

You can Expand \( (x-3)^2 \) through the use of formula and multiplication.

Expand \( (x-3)^2 \) through Multiplication method.

=> \( (x-3)^2 \) [ we can write ]
=> \( (x-3)^2 = (x-3)(x-3) \) [simplify]

=> \( (x-3)^2 = x(x-3) – 3(x-3) \)


=> \( (x-3)^2 = x^2 – 3x – 3x + 9) \)

=> \( (x-3)^2 = x^2 – 6x + 9) \)

Expand \( (x-3)^2 \) through Formula.  \( (a-b)^ =a^2 -2ab + b^2 \)

=> \( (x-3)^2 = x^2 – 2 \times x \times 3 + 3^2 \)

=> \( (x-3)^2 = x^2 – 6x + 9 \)

Expand Form of \( (x-3)^2 = x^2 – 6x + 9 \)

 

Continue Reading
Advertisement